Effects of NPK and ALA on endogenous hormones of Leymus chinensis (Trin.) Tzvel under drought stress - Zong, Xuefeng; Lv, Jun; Anjum, Shakeel Ahmad; Wu, Xiao; Wu, Chao; Li, Yunpeng; Wang, Sangen (Bangladesh Journal of Botany, 2021)
An experiment was conducted to elucidate the negative impacts of drought on growth and hormones of Leymus chinensis. Results showed that plant height, dry weight and zeatin riboside contents declined under drought condition over the control. Whereas indole acetic acid, gibberellic acid and abscisic acid contents were augmented under stress environment over the normal conditions. Exogenous application of NPK and/or 5-aminolevulinic acid (ALA) depicted more pronouncing response to alleviate adversities of drought. Conclusively, foliar application of 'Urea (1%) + KH2PO4 (1%) + ALA (50 mg/l)' produced better results under drought stress on the evaluated parameters.